동종 조혈모세포 이식 전후 영양상태 평가 - 박미영(Park, Mi Young); 박정윤(Park, Jeong Yun) (Asian oncology nursing, 2012)
Purpose: This study was performed to identify the pre-and post-transplant nutritional assessment for patients undergoing allogeneic hematopoietic stem cell transplantation (HSCT). Methods: The subjects of this study were 25 patients undergoing allogeneic HSCT. The data collection was performed from January 31st to March 31st, 2011. The Patient-Generated Subjective Global Assessment (PG-SGA), anthropometrics and biochemical test were collected from the time they entered the isolation unit until they left. Results: Pre-transplant nutritional assessment status indicated moderate malnutrition which scored $7.32{±}1.68$ in PG-SGA. There were 22 patients (88.0%) with moderate malnutrition and 3 patients (12.0%) with severe malnutrition. Post-transplant nutritional assessment indicated severe malnutrition status which scored $11.92{±}3.26$ in PG-SGA. Pre-and post-transplant nutritional assessment displayed significant differences (p<.001) in PG-SGA score. Hematopoietic stem cell transplantation led to a deterioration of patients' nutritional status. Pre-transplant patients were already in malnutrition status and patients undergoing allogeneic HSCT were at risk for malnutrition. Conclusion: Pre-and post-transplant patients were categorized as having undernutritional and malnutritional status. Pre-transplant nutrition status impacted on post-transplant nutritional status. Health care personnel should pay attention to patient's nutrition status when undergoing allogeneic HSCT with appropriate nutritional assessment tools.